The caves of steel - Asimov, Isaac, 1920-1992 (Asimov, Isaac, 1920-1992. Robot series, 2018)
The first of Asimov's robot novels, chronicling the unlikely partnership between a New York City detective and a humanoid robot who must learn to work together. Detective Elijah Baley invesitgates the murder of an offworlder in Spacetown. In the opinion of the Spacers, the murder is tied up with recent attempts to sabotage the Spacer-sponsored project of converting Earth to an integrated human/robot society on the model of the Outer Worlds. To search for the killer in the City's vast caves of steel, Elijah is assigned a Spacer partner named R. Daneel. That's Robot Daneel. And notwithstanding the celebrated Three Laws of Robotics, which should make such a murder impossible, R. Daneel is soon Elijah's prime suspect.